Language Usage, Participation, Employment and Earnings: Evidence for Foreigners in West Germany with Multiple Sources of Selection - Stephan L. Thomsen; Johannes Gernandt; Alisher Aldashev (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Language proficiency may not only affect the earnings of the individual, but the probability to participate in the labor market or becoming employed as well. It may also affect selection of people into economic sector and occupation. In this paper, the effects of language proficiency on earnings are analyzed for foreigners in Germany with joint consideration of up to four types of selection. The results show that language proficiency significantly increases participation and employment probability and affects occupational choice. When selection into economic sector and occupation is regarded, we do not find an impact of language ability on earnings thereby implying an indirect effect.
Keywords: J61; J24; J15; C35; 330; Foreigners; Participation; Employment; Language Ability; Multiple Selection; Migranten; Mehrsprachigkeit; Berufliche Integration; Einkommen; Deutschland; self-selection bias